18.1k views
3 votes
PLEASE HELP

For the graphed function f(x) = −(3)x − 1 + 3, calculate the average rate of change from x = 1 to x = 3.

PLEASE HELP For the graphed function f(x) = −(3)x − 1 + 3, calculate the average rate-example-1
User Xinthink
by
5.9k points

2 Answers

5 votes
the formula would be ( f(x2) -f(x1) ) / ( x2 - x1 ) f(x2)= -6 , f(x1) = 2 , x2= 3 , x1= 1. so that is : (-6 - 2 ) / (3-1) = -8/2 = -4
User Mthurlin
by
5.7k points
6 votes

Answer:

The average rate of change is
-4

Explanation:

The given function is
f(x)=-3^(x-1)+3.

We want to find the average rate of change of this function from
x=1 to
x=3.

This is the slope of the secant line joining the points
(1,f(1)) and
(3,f(3)).

From the graph,
f(1)=2 and
f(3)=-6

The average rate of change


=(f(3)-f(1))/(3-1)


=(-6-2)/(3-1)


=(-8)/(2)


=-4

User Kenmore
by
6.2k points